Expression of cysteinyl leukotriene receptor 1 in human traumatic brain injury and brain tumors - Zhang, Wei-Ping; Hu, Hua; Zhang, Lei; Ding, Wei; Yao, Hong-Tian; Chen, Ke-Da; Sheng, Wen-Wen; Chen, Zhong; Wei, Er-Qing (Neuroscience letters, 2004)
Cysteinyl leukotrienes (CysLTs) are potent proinflammatory mediators. CysLT receptor 1 (CysLT 1) is one of the two CysLT receptors that has been cloned. Although the expression of CysLT 1 in the brain has been demonstrated by Northern blot and RT-PCR analyses, the location of CysLT 1 in the brain remains unknown. The objective of this study was to examine the distribution of CysLT 1 by immunohistochemical analysis in human brains with traumatic injury or tumors. CysLT 1 was expressed intensely in the microvascular endothelial cells in both normal and abnormal conditions. At 8 days after traumatic injury, microvascular regeneration was found and all of the endothelial cells highly expressed CysLT 1. In gray and white matters of the normal regions of the brain, CysLT 1 was expressed weekly or not at all. However, the CysLT 1 expression increased in the neuron- and glial-appearing cells in gray and white matters after traumatic brain injury. CysLT 1 was also detected in astrocytoma, ganglioglioma and metastatic adenocarcinoma, and the expression in the neuron- and glial-appearing cells around brain tumors increased robustly.